Pelaksanaan Stimulasi Mencegah Lansia Pikun Dan Kurang Teliti Melalui Latihan Aktivitas Brain Gym Di Program Sekolah Lansia Desa Sliyeg Kecamatan Sliyeg Kabupaten Indramayu - Masliha (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Everyone who is blessed with a long life will definitely experience old age. One of the problems that occurs in the elderly is dementia. Dementia is a disorder that occurs as a result of physiological changes in the form of cognitive decline. To overcome this, include brain exercises. Brain gym is a series of simple and fun movements that are used to improve learning abilities by using the whole brain. This research is quantitative research using a quasi-experimental method with a one group pretest - posttest approach. The population is 56 elderly people in the elderly school program in Sliyeg Village, Sliyeg District, Indramayu Regency. Samples were taken using accidental sampling. The research was carried out from April 3 – June 30 2023. Research results: the level of dementia before the Brain Gym Stimulation action was carried out was 19 people (73.1%) experiencing moderate levels and the level of dementia after the Brain Gym Stimulation action was carried out as many as 23 people (88.5%) were in the mild category and the results of the Paired Samples t Test The test shows that the average difference between the level of dementia before and after the brain gym stimulation was 2.615. This means that there was a decrease in the level of dementia after the intervention with an average decrease of 2.6 points. The result of calculating the